Characterization of complete chloroplast genome of Amentotaxus yunnanensis (Taxaceae), a species with extremely small populations in China. Issue 1 (2nd January 2019) - Ge, Jia; Bi, Guiqi; Luo, Guifen
Abstract: Amentotaxus yunnanensis H. L. Li (Taxaceae) is a threatened plant species and a typical Plant Species with Extremely Small Population (PSESP). In this study, we sequenced the whole chloroplast (cp) genome of A. yunnanensis . The results showed that the plastid genome is 137, 594 bp in size. In total, 118 unique genes were annotated, including 83 protein-coding genes, 31 tRNA genes, and four rRNA genes. The phylogenetic tree based on 24 cp genomes of Taxaceae support the close relationships of the genera Amentotaxus and Torreya .